2017
DOI: 10.29252/nrip.irj.15.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Improving Voice Outcomes After Injury to the Recurrent Laryngeal Nerve

Abstract: Objectives: The present study aimed to determine the voice outcomes before and after the administration of voice therapy in patients who suffered an injury to the recurrent laryngeal nerve after undergoing thyroidectomy. Methods:The sample consisted of 26 patients (2 males and 24 females) aged between 18 and 80 years (m=55±12) who experienced injury to the recurrent laryngeal nerve following thyroidectomy that was used to treat a thyroid gland disease. Subjective and objective parameters of the voice of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Similar conclusions have already been reported by Žunić et al (2017), who observed a decrease in the noise-to-harmonic ratio (NHR) after voice nerve therapy in patients with recurrent laryngeal nerve injury ( 19 ). Cantarella et al (2010) also observed a decrease in the NHR three months after voice therapy in patients with vocal cord paralysis and concluded that the therapy was able to achieve minimal spontaneous glottal compensation ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similar conclusions have already been reported by Žunić et al (2017), who observed a decrease in the noise-to-harmonic ratio (NHR) after voice nerve therapy in patients with recurrent laryngeal nerve injury ( 19 ). Cantarella et al (2010) also observed a decrease in the NHR three months after voice therapy in patients with vocal cord paralysis and concluded that the therapy was able to achieve minimal spontaneous glottal compensation ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, RLN transection impaired the frequency bandwidth of many call types at 1 WPS. These findings suggest that mice with unilateral VF paralysis lose the ability to modulate the frequency in their calls, similar to human patients who experience impairment in their phonation frequency (i.e., pitch range) following injury (Junuzovic‐Zunic, Ibrahimagic, Altumbabic, Umihanic, & Izic, ; Sridhara, Ashok, Raghunathan, & Mann, ; Xue, Mittal, Zheng, & Bielamowicz, ). Unilateral VF paralysis patients also demonstrate impaired maximum phonation times (Sridhara et al, ), which was observed in the current study as decreased call durations and durations of peak frequency in a collection of call types in RLN transected mice.…”
Section: Discussionmentioning
confidence: 68%